Penguatan Literasi Digital dan Branding Penulis Perempuan melalui Pendampingan Pemasaran Konten Berbasis 5A - Arofah, Rifka Utami; Hidayati, Noor Kholifah; Mintarti, Mintarti; Rahma, Zaida Aqiela; Nida, Abidah Fahimatun (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance digital literacy and branding skills among female writers through a 5A content marketing–based approach for members of Nasyiatul ’Aisyiyah in Banyumas Regency. The program was implemented using demonstration and discussion methods, with data collected through questionnaires and analyzed using the Wilcoxon test. The results indicate a positive improvement in participants’ digital marketing literacy, with a 75% increase reflected in higher post-test scores compared to pre-test scores. The findings also suggest a shift in participants’ perspectives regarding the role of writers in the digital era, which extends beyond text production to include personal branding development and community engagement through social media platforms such as Instagram and TikTok. These outcomes highlight the importance of integrating content marketing strategies into digital literacy programs for writers.